Spillover Effects of Digital Infrastructure and Financing - Yoshino, Naoyuki; Siregar, Tifani Husna; Azhgaliyeva, Dina (Journal of Infrastructure Policy and Management (JIPM), 2022)
This article proposes a tax sharing scheme between governments and private sector investors of Information and Communications Technology (ICT) infrastructure. The current COVID-19 pandemic has not only emphasized the crucial need of ICT infrastructure development, but has also expanded government budget deficits in many countries. Therefore, participation from the private sectors is necessary to close the widening investment gap in ICT infrastructure. One of the measures to attract private sectors’ involvement in ICT infrastructure is by creating a steady stream of income for the investors. To ensure the success of the proposed financing scheme, this article also recommends the development of supporting hard and soft infrastructure as well as the digitalization of tax reporting systems